Fat and cholesterol meat of briler chicken feed by step down protein with addition lime juice as acidifier - Hasanuddin, Sumaiya; Yunianto, Vitus Dwi; Tristiati, . (Buletin Nutrisi dan Makanan Ternak, 2013)
The aim of  research is to produce low fat and cholesterol in broiler meat with given lime juice (APJN) and citric acid (AS) as acidifier in step down protein feeding system, without interfering function of digestive tract of broiler. The material used were 192 birds DOC (day old chick) Hubbard strain MB 202 "unsex" . Research using CRD (completely randomized design) with 6 treatments and 4 replications, and there are 24 experimental units. Each experimental unit consisted of 8 chick broiler. Treatments were P0 (control diet (without step down)), P1 (step down diet), P2 (step down + citric acid 0.8%), P3 (step down + lime acid 0.4 % (6.9 ml/100g feed)) P4, (step down + lime  acid 0.8% (13.8 ml/100g feed)) and P5 (step down + lime acid 1.2% ( 20.7 ml/100g feed)). Parameters measured in this research were fat and cholesterol in broiler meats. The data were subjected to analysis by software SPSS 16, to determine the effect of treatment. If the treatment was significant it continued to Duncan test . The results showed that  step down protein feeding system  with given lime juice as acidifier were significant effect (P <0.05) to decrease cholesterol meat (mg/g) with an average (0.99, 0.89, 1.11, 1.02, 1.03 and 0.81), but no effect (P> 0.05) to decrease fat meat (%) with a mean (5.53, 6.30, 6.13, 6.15, 7.38 and 4.8) .